Importance of status quo when lobbying a coalition government - Refik Emre Aytimur (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
Lobbying a coalition government is different than lobbying a single-party government, since in the case of a coalition government, the interest group can intervene in the intragovernmental decision process. In the case where the interest group likes the status quo more than the surplus maximizing policy, the interest group influences the policy without any contribution thanks to its credible threat to block unfavorable proposals. We show further that when, say, a leftist coalition government may be replaced by a rightist coalition government, the final policy reflects a rightist interest group's preferences more heavily due to the interest group's forward-looking considerations.
Keywords: C78; D72; D78; 330; lobbying; policy-making; coalition governments; status quo